Does attending preschool in an economically advantaged or disadvantaged neighborhood moderate the effects of the preschool edition of promoting alternative thinking strategies®? - Kapetanovic, Sabina; Ginner Hau, Hanna; Eichas, Kyle; Olsson, Tina M.; Ferrer-Wreder, Laura; Eninger, Lilianne (Frontiers in Education, 2022)
Early interventions that foster the participation, engagement, and development of children attending preschools, including those in economically disadvantaged neighborhoods, are of high priority. One such intervention is a universal socioemotional learning (SEL) program called Promoting Alternative Thinking Strategies (PATHS®) which aims to promote social emotional competence and positive adjustment in children. In the SEL field, areas in need of exploration include the possible role that neighborhood income level could have for children’s social emotional competence and positive adjustment and how neighborhood income level may relate to benefits of an intervention such as PATHS. The study aims were to investigate 1) the baseline group differences in social emotional competence and adjustment depending on the neighborhood income level and 2) to determine if neighborhood income level moderated the effects of PATHS on children’s social emotional competence and adjustment from pre to posttest. Participants were 275 children aged four to five years old, from the preschools randomized into an immediate intervention (n = 145 children) or a wait-list control group (n = 130 children). Overall, 42.9 % (n = 118) of the children attended preschools in economically disadvantaged neighborhoods and 57.1 % (n = 157) of the children attended preschools in economically advantaged neighborhoods. Children’s social emotional competence and adjustment were assessed through child tasks, child observations and teacher reports. The moderation of intervention effects by the preschools’ neighborhood income was tested in a series of just-identified structural equation models (SEM) that explored interaction effects (income*PATHS interactions). At baseline, relative to children attending preschool in economically advantaged neighborhoods, children attending preschool in economically disadvantaged neighborhoods showed lower levels of inhibitory control, working memory, task orientation and higher levels of inattention. Children attending preschools in economically disadvantaged neighborhoods participating in PATHS showed reductions in inattention, social withdrawal and anxiety compared to control group children. Additionally, PATHS children from advantaged neighborhoods improved their prosocial behavior, but not their social independence, relative to control group children. Offering PATHS as an SEL intervention in early childhood education and care settings could help to reduce disparities among children in a number of key outcomes.